Explaining Students’ Achievement Motivation Based on Trust in Professors and Perseverance with the Mediating Role of Academic Self-Regulation - Parsai Moghadam, Marzieh; Khanjani, Mehdi; Borjali, Ahmad (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2026)
Objective: This study aimed to explain students’ achievement motivation based on trust in professors and perseverance, emphasizing the mediating role of academic self-regulation. Methods and Materials: A correlational design using path analysis was employed. The sample comprised 219 students (128 males, 91 females; mean age years). Data were collected using Hermans’ Achievement Motivation Questionnaire, the Trust in Professors subscale of Moran and Tschannen-Moran’s Academic Optimism Scale, Zimmerman and Pons’ Academic Self-Regulated Learning Strategies Questionnaire, and Duckworth’s Perseverance (Grit) Scale. The structural equations and mediation effects were analyzed using AMOS-26 software and the bootstrapping method. Findings: The proposed path model demonstrated an optimal statistical fit ( , , ). Results indicated that trust in professors ( ) and perseverance ( ) had significant direct positive effects on achievement motivation. Furthermore, academic self-regulation directly impacted achievement motivation ( ) and significantly mediated the relationship between trust in professors (indirect ), perseverance (indirect ), and achievement motivation. Overall, the model explained of the variance in achievement motivation. Conclusion: Trust in professors and individual perseverance are fundamental factors that both directly and indirectly enhance students’ achievement motivation. Academic self-regulation serves as a pivotal bridging mechanism in this dynamic, playing a crucial role in boosting student motivation.